Validation of the Beck Depression Inventory for a Portuguese-speaking Chinese community in Brazil - Wang,Y.-P. (2005)
The objective of the present study was to investigate the psychometric properties and cross-cultural validity of the Beck Depression Inventory (BDI) among ethnic Chinese living in the city of São Paulo, Brazil. The study was conducted on 208 community individuals. Reliability and discriminant analysis were used to test the psychometric properties and validity of the BDI. Principal component analysis was performed to assess the BDI's factor structure for the total sample and by gender. The mean BDI score was lower (6.74, SD = 5.98) than observed in Western counterparts and showed no gender difference, good internal consistency (Cronbach's alpha 0.82), and high discrimination of depressive symptoms (75-100%). Factor analysis extracted two factors for the total sample and each gender: cognitive-affective dimension and somatic dimension. We conclude that depressive symptoms can be reliably assessed by the BDI in the Brazilian Chinese population, with a validity comparable to that for international studies. Indeed, cultural and measurement biases might have influenced the response of Chinese subjects.